Mapeamento do processo de recurso de apelação cível e a inter-relação entre os sistemas PJ-e e MPV2 no Tribunal de Justiça da Paraíba e no Ministério Público da Paraíba: possíveis entraves técnicos - Araujo, Geraldo Maciel de (2023)
The slowness of the Brazilian judicial system in its typical jurisdictional function and the response of its services to society is a problem that plagues the public administration for centuries, resulting in numerous attempts to achieve a viable and satisfactory solution. This condition justifies the choice of the theme for the production of this work, because, starting from the analysis of the movement of the Civil Appeal, we sought to understand the possible obstacles and or obstacles causing the slowness of the procedural march in the second degree of jurisdiction, having as an environment of analysis of the interrelation of the technological systems of the Judiciary (PJ-e) and the Public Prosecutor's Office (MPV2), adopting the jurisdiction of the State of Paraíba and its limits of action as a model of study. Methodologically we used the qualitative approach, with ex ploratory, descriptive and explanatory objectives, with bibliographic, documentary and case study research procedures. In mapping the process, we used techniques of business administration and its monitoring systems and production studies, arriving at the graphic model of what would be the path taken by the judicial process with well-defined steps with beginning, middle and end. As a result, already at the beginning of this research, we were able to identify the first critical points of the procedural movement, characterized, redundantly, by the reflection of the failure of the operator of the Law or servers of the organs involved, added to the incidents of the process. We conclude then, among other reasons, that problems of lack of automation in some stages, complicated and non-universal taxonomy, inconsistency and latency of the data transmission system and lack of interoperability between the PJ-e systems and other systems, without exhausting all possibilities, are causes that provoke the delay of response by the judiciary in its mister of private body to the judgment of public and / or private demands.